1986
DOI: 10.1007/bf02471080
|View full text |Cite
|
Sign up to set email alerts
|

Omental transposition and skin graft in patients for advanced or recurrent breast cancer

Abstract: Nine patients, including 4 with primary advanced breast cancer (stage IV) and 5 with local recurrent cancer, underwent chest wall reconstruction using an omental flap and mesh skin grafting. In 2 of these patients the defect of bony chest wall was reconstructed with an acryl-resin plate and omental flap. The postoperative course in all patients was uneventful, except for a slight necrosis on the transposed mesh skin. Flail chest or dyspnea did not occur in those with a bony chest wall reconstruction. The immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In that study, the HRQoL improved due to the treatment. 11 Furthermore, in a study by Toija et al, after treatment of breast cancer (without chest wall resection and reconstruction), the mean 15D HRQoL score was 0.886. 24 Rautalin et al found that the mean 15D HRQoL score after treatment of breast cancer is 0.91.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In that study, the HRQoL improved due to the treatment. 11 Furthermore, in a study by Toija et al, after treatment of breast cancer (without chest wall resection and reconstruction), the mean 15D HRQoL score was 0.886. 24 Rautalin et al found that the mean 15D HRQoL score after treatment of breast cancer is 0.91.…”
Section: Discussionmentioning
confidence: 98%
“…7 Few previous studies assessing HRQoL in patients after chest wall tumor resection all have some limitations. [8][9][10][11][12] They are hampered by small sample size 8,9,11,12 ; fail to compare results obtained in patients to those of a healthy control population 8 , 10-12 ; or do not report the extent of the surgical operations, need for reconstruction, and methods of reconstruction. 9,10 There are no studies assessing postoperative HRQoL of patients with chest wall sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…The greater omentum is attached inferiorly to the transverse colon after making a loop over itself forming a four layer loop. Superiorly, it is attached to the greater curve of the stomach (Figure 2) [20][21][22].…”
Section: Anatomic Considerationsmentioning
confidence: 99%
“…In addition, resections for recurrent breast cancer and post-radiation ulcers also result in extensive skin loss with or without chest wall defects. Several methods have been tried during the last four decades, including skin grafts, local flaps, omental flaps, abdominal flaps, and myocutaneous (MC) flaps to cover soft tissue defects following surgery for LABC and recurrent breast cancer [3][4][5][6][7]. The aim of reconstruction in this group should be an expeditious and simple closure with good quality skin cover so that they can receive early post-operative radiation with minimal morbidity.…”
Section: Introductionmentioning
confidence: 99%